Chapter 4 Against Unconscious Volition - Bayne, Tim (Taylor & Francis, 2024)
This chapter examines the question of whether mental categories come in both conscious and unconscious forms, focusing on the case of volition. Drawing out the implications of the fact that volition is a personal-level phenomenon, an argument against the possibility of unconscious volition is developed. Three objections to that argument are then considered: the first appeals to minimal actions and the exercise of expertise; the second appeals to Benjamin Libet's studies regarding the Readiness Potential; and the third appeals to relational conceptions of consciousness. All three arguments are found to be uncompelling. The chapter concludes by revisiting the question of whether mental categories can, in general, take both conscious and unconscious forms.